KETERAMPILAN PETANI DALAM PENGENDALIAN HAMA TERPADU DI DESA GUNUNG BATU, KABUPATEN OKU TIMUR - Ali Alamsyah Kusumadinata; Astrid Sri Wahyuni Sumah (Indonesian Journal of Agricultural Economics, 2023)
While the importance of biological control for crop production is widely recognized, research on how farmers view predatory insects in eradicating pests on agricultural land is still rare. Although there is much ecological research on predatory beetles as part of biological control, little social research has been conducted on the critical level of understanding of biological control and the organisms involved. This research examines farmers' understanding of using predatory beetles as a biological control concept on agricultural land in Gunung Batu Village, East OKU Regency. Therefore, this research aims to see how farmers' skills are in managing integrated pest control using predatory Coleoptera beetles in managing rice cultivation. The research results show that farmers still use predatory beetles as part of controlling pest populations on agricultural land. Farmers consider predatory beetles to prevent pest outbreaks that can harm quality rice production. So, farmers can build a network of farmers so they can learn from each other and share local knowledge. Apart from that, the results obtained from integrated pest control, farmers can experience positive results and can positively influence farmers' perceptions of natural enemies of agricultural pests. Keywords: Agricultural pests, Coleoptera beetles, biological control, predators